Kajian Kandungan Sedimen Pada Muara Sungai Pantai Pasir Putih Desa Sukajaya Cilamaya Kulon Kabupaten Karawang - Agus Riyadi (DPPM Universitas Pelita Bangsa, 2022)
The river is the place where the sediment transport process takes place. One of the mechanisms of the sediment transport process is by floating in the form of suspension loads. Factors that affect the magnitude of the suspension load include flow discharge and rainfall. The study was conducted at the estuary of the white sandy beach in Sukajaya village with the aim of analyzing the relationship between flow discharge and suspension discharge, and analyzing the total amount of suspension load. The method used in this study is a survey method and field measurements in the form of measuring river water level, flow discharge, and taking suspension samples. sedimentation samples were analyzed in the laboratory to determine the concentration of the suspension. The results showed 1) The relationship between flow discharge and suspension discharge had a strong correlation, but did not have a large effect. 2) Rainfall does not directly affect the amount of suspension discharge. 3) The total amount of suspended cargo flowing through the estuary reaches 218,560 tons/year. Keywords : Flow discharge, Suspension sediment, River